Wet Laboratory Versus Computer Simulation for Learning Endobronchial Ultrasound: A Randomized Trial - David R Stather; Paul MacEachern; Alex Chee; Elaine Dumoulin; Christopher A Hergott; Alain Tremblay (Canadian Respiratory Journal)
BACKGROUND: Linear endobronchial ultrasound with transbronchial needle aspiration (EBUS-TBNA) is a revolutionary bronchoscopic procedure that is challenging to learn.